Interconnecting the violences of men: continuities and intersections in research, policy, and activism - Seymour, Kate (Interconnecting the violences of men, 2025)
The introductory chapter provides a rationale for the book, outlining how the gendering of men’s violence in specific fields has failed to consider the interconnections, intersections, and continuities between these fields. Naming only some violences as gendered enables other violences to go unmarked. We argue that that all violences are gendered, even when they are not perpetrated by men. We review the key issues in specific fields of gendered violences, including men’s violence against women, children and young people, other men, gay, trans and non-binary people, disabled people and men’s violence against themselves. We also consider how gendered violence is enacted through colonialism, militarism and war, and in relation to non-human animals and the environment, as well as through epistemic injustice. We conclude the chapter with a substantive guide to the chapters by our contributors who, from a diverse range of disciplinary backgrounds, foreground specific fields of gendered violence and explore their interconnections with other violences enacted by men.